Methylation differences at the HLA-DRB1 locus in CD4+ T-Cells are associated with multiple sclerosis. (July 2014) - Graves, MC; Benton, M; Lea, RA; Boyle, M; Tajouri, L; Macartney-Coxson, D; Scott, RJ; Lechner-Scott, J
Background: Multiple sclerosis (MS) is thought to be caused by T-cell mediated autoimmune dysfunction. Risk of developing MS is influenced by environmental and genetic factors. Modifiable differences in DNA methylation are recognized as epigenetic contributors to MS risk and may provide a valuable link between environmental exposure and inherited genetic systems. Objectives and methods: To identify methylation changes associated with MS, we performed a genome-wide DNA methylation analysis of CD4+ T cells from 30 patients with relapsing–remitting MS and 28 healthy controls using Illumina 450K methylation arrays. Results: A striking differential methylation signal was observed at chr. 6p21, with a peak signal at HLA-DRB1 . After prioritisation, we identified a panel of 74 CpGs associated with MS in this cohort. Most notably we found evidence of a major effect CpG island in DRB1 in MS cases ( pFDR < 3 × 10 −3 ). In addition, we found 55 non-HLA CpGs that exhibited differential methylation, many of which localise to genes previously linked to MS. Conclusions: Our findings provide the first evidence for association of DNA methylation at HLA-DRB1 in relation to MS risk. Further studies are now warranted to validate and understand how these findings are involved in MS pathology.